1977
DOI: 10.1227/00006123-197707000-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Infratentorial-Supracerebellar Exposure of Tumors in the Pineal Area

Abstract: Nine pineal area lesions were operated upon by the infratentorial-supracerebellar approach. There was one operative death and one death due to disseminated germinoma recurrence 2 1/2 years postoperatively. The remaining seven patients have shown no sign of recurrence and are neurologically normal. The surgical method that has evolved through these nine cases is discussed. The infratentorial-supracebebellar exposure is an excellent one for lesions in the region of the pineal gland, posterior 3rd ventricle, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The infratentorial supracerebellar (ITSC) approach (10)(11)(12) and the occipital transtentorial (OTT) approach (13)(14)(15) are the standard approaches for the microsurgical resection of pineal-region tumors. The ITSC approach is a midline approach and provides definite orientation of the tumor and surrounding structures (16).…”
Section: Selection Of Surgical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The infratentorial supracerebellar (ITSC) approach (10)(11)(12) and the occipital transtentorial (OTT) approach (13)(14)(15) are the standard approaches for the microsurgical resection of pineal-region tumors. The ITSC approach is a midline approach and provides definite orientation of the tumor and surrounding structures (16).…”
Section: Selection Of Surgical Approachmentioning
confidence: 99%
“…On the other hand, Page reported that severe cerebellar swelling occurred after the division of all vermian bridging veins and one hemispheric bridging vein. He strongly advocated the importance of preserving the hemispheric bridging veins (12). We always divide only the thin bridging veins and try to preserve the thick ones.…”
mentioning
confidence: 99%
“…In the majority of my cases with pineal tumors, I have chosen the supracerebellar infratentorial approach, which constitutes the most common access route to the pineal region [7]. To avoid excessive downward retraction of the superior cerebellar vermis, I used the paraculminal route either on one side or bilaterally.…”
Section: Choice Of Surgical Approachmentioning
confidence: 99%
“…Under microscope magnification, severing the bridging veins between cerebellum and tentorium is a crucial point to gain the corridor carrying out the approach through. As some authors reported (Ueyama et al, 1998;Bruce & Stein, 1993;Fain et al, 1994;Page 1977), bridging veins in the midline can be sacrificed but this could lead to cerebellar venous infarction and consequent swelling. The arachnoidal adhesions should be released on the surface of cerebellum and all along the tentorial incisura as well, where they are particularly thickened.…”
Section: Infratentorial-supracerebellar Approachmentioning
confidence: 99%